The Impact of Using Translation of The Animated Movies on EFL Young Learners - Ben Khalil , Rataj Moftah; Salem, Mona M. M. (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
This research studies the impact of using translation of animated movies on young learners in their vocabulary, pronunciation, and culture, also identifies the use of films on young learners and by teachers in their classroom. The second section shows some previous studies that support the research. The Third focus is on how data was collected in this study is a questionnaire directed to a sample of 13 teachers who were selected from the Faculty of Human Science. In addition, the other directed from questionnaire and observations to a sample of 52 young learners who were selected from three schools in Libya (Zliten) to provide a deeper analysis on the impact of using translation of cartoon films on young learners. The results of those data showed that many teachers have a positive attitude about the use of translation movies, including developing vocabulary and consolidating it in the minds of students and the correct pronunciation of words, as well as developing listening and speaking skills. Because of its long-lasting impact on young students. Based on the results of the analysis, some recommendations for teachers in schools come from research students at Alasmarya Islamic University about the intensification of the use of the translation of animated movies and strategies for young students and another recommendation for educational institutions about producing translation cartoon films for young learners within the educational curriculum.
Keywords: Using translated movies; English vocabulary; Pronunciation